Alcohol, marijuana, and opioid use disorders: 5-Year patterns and characteristics of emergency department encounters. Issue 1 (2nd January 2018) - Bahorik, Amber L.; Satre, Derek D.; Kline-Simon, Andrea H.; Weisner, Constance M.; Young-Wolff, Kelly C.; Campbell, Cynthia I.
ABSTRACT: Background : Changes in substance use patterns stemming from opioid misuse, ongoing drinking problems, and marijuana legalization may result in new populations of patients with substance use disorders (SUDs) using emergency department (ED) resources. This study examined ED admission trends in a large sample of patients with alcohol, marijuana, and opioid use disorders in an integrated health system. Methods : In a retrospective design, electronic health record (EHR) data identified patients with ≥1 of 3 common SUDs in 2010 ( n = 17, 574; alcohol, marijuana, or opioid use disorder) and patients without SUD ( n = 17, 574). Logistic regressions determined odds of ED use between patients with SUD versus controls (2010–2014); mixed-effect models examined 5-year differences in utilization; moderator models identified subsamples for which patients with SUD may have a greater impact on ED resources. Results : Odds of ED use were higher at each time point (2010–2014) for patients with alcohol (odds ratio [OR] range: 5.31–2.13, P s < .001), marijuana (OR range: 5.45–1.97, P s < .001), and opioid (OR range: 7.63–4.19, P s < .001) use disorders compared with controls; odds decreased over time ( P s < .001). Patients with opioid use disorder were at risk of high ED utilization; patients were 7.63 times more likely to have an ED visit in 2010 compared with controls and remained 5.00 (average) times more likely to use ED services. ED use increased at greater rates for patients with alcohol and opioid use disorders with medical comorbidities relative to controls ( P s < .045). Conclusions : ED use is frequent in patients with SUDs who have access to private insurance coverage and integrated medical services. ED settings provide important opportunities in health systems to identify patients with SUDs, particularly patients with opioid use disorder, to initiate treatment and facilitate ongoing care, which may be effective for reducing excess medical emergencies and ED encounters.